Remote Ischemic Perconditioning to Reduce Reperfusion Injury During Acute ST‐Segment–Elevation Myocardial Infarction: A Systematic Review and Meta‐Analysis. Issue 5 (May 2017) - McLeod, Shelley L.; Iansavichene, Alla; Cheskes, Sheldon
Abstract : Background: Remote ischemic conditioning (RIC) is a noninvasive therapeutic strategy that uses brief cycles of blood pressure cuff inflation and deflation to protect the myocardium against ischemia–reperfusion injury. The objective of this systematic review was to determine the impact of RIC on myocardial salvage index, infarct size, and major adverse cardiovascular events when initiated before catheterization. Methods and Results: Electronic searches of Medline, Embase, and Cochrane Central Register of Controlled Trials were conducted and reference lists were hand searched. Randomized controlled trials comparing percutaneous coronary intervention (PCI) with and without RIC for patients with ST‐segment–elevation myocardial infarction were included. Two reviewers independently screened abstracts, assessed quality of the studies, and extracted data. Data were pooled using random‐effects models and reported as mean differences and relative risk with 95% confidence intervals. Eleven articles (9 randomized controlled trials) were included with a total of 1220 patients (RIC+PCI=643, PCI=577). Studies with no events were excluded from meta‐analysis. The myocardial salvage index was higher in the RIC+PCI group compared with the PCI group (mean difference: 0.08; 95% confidence interval, 0.02–0.14). Infarct size was reduced in the RIC+PCI group compared with the PCI group (mean difference: −2.46; 95% confidence interval, −4.66 to −0.26). Major adverse cardiovascular events were lower in the RIC+PCI group (9.5%) compared with the PCI group (17.0%; relative risk: 0.57; 95% confidence interval, 0.40–0.82). Conclusions: RIC appears to be a promising adjunctive treatment to PCI for the prevention of reperfusion injury in patients with ST‐segment–elevation myocardial infarction; however, additional high‐quality research is required before a change in practice can be considered.